Antioxidant Activity from the Combination of Ethanolic Extract of Tea Leaves (Camellia sinensis) and Soursop Leaves (Annona muricata l.) and Optimation of the Effervescent Granule Production - Fatma Sari Masitha; Rifki Febriansah (Universitas Muhammadiyah Yogyakarta, 2019)
Soursop Leaves (Annona muricata L.) and Tea Leaves (Camellia sinensis) are plants that contain flavonoids which are considered to act as antioxidants and can become chemopreventive agents. This study aims to identify the potential of Soursop Leaves and Tea Leaves as chemopreventive agents. The first stage of this research was to determine the presence of flavonoids in both of ethanolic extract using TLC method. The second stage is to examine the antioxidant activity of the combination of ethanolic extract of soursop leaves and tea leaves against free radical DPPH (1,1-diphenyl-2-pikrihidrazil). Docking molecular test of acetogenin and catechin compounds at HER-2 and ER-α receptors which are biomarkers of breast cancer. Furthermore, the optimization of effervescent granule production using moist granulation method is carried out. The result shows that ethanolic extract of soursop leaves and tea leaves contains flavonoid shown with Rf value of 0.66 and 0.68, and the comparison of Rf 0.66. The combination of both ethanolic extract has very strong antioxidant activity with IC50 value 26,90 μg/mL. The result of molecular docking of acetogenin and catechin compounds at HER-2 receptors shows respective docking score of -6.3 kcal/mol and -6.7 kcal/mol while ER-α receptors shows a docking score of -6.5 kcal/mol and -7.6 kcal/mol. In addition, the most optimal effervescent granule production is formula four with physical test result such as moisture content of 1.07% with a dissolve time of 45.5 seconds and acidity of 6.18. The result shows that ethanolic extract of soursop leaf (Annona muricata L.) and Tea Leaves (Camellia sinensis) have potential activity as chemopreventive agents and can be formulated into effervescent granule production.